2011
DOI: 10.1063/1.3585782
|View full text |Cite
|
Sign up to set email alerts
|

Optical bistability in mesoporous silicon microcavity resonators

Abstract: Porous silicon (PSi) has been shown to be a material with varieties of nonlinear optical properties. These properties have been discussed in terms of its nature of photoluminescence mechanism such as quantum confinement, surface states and the role of impurities. PSi has also been shown to be a useful material for optical devices, and have potential applications in fields such as bio-sensing and efficient lighting. In the following thesis, I present my theoretical and experimental results in studying a nonline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 170 publications
0
2
0
Order By: Relevance
“…When the nonlinearity is saturating, it can be shown that if ∆n is the maximum refractive index change, then the condition for bistability is ∆nk o L > αL + (1-R eff ), where α is the (unsaturable) loss per unit length inside the cavity and R eff is the average mirror reflectivity (Garmire, 1989). Semiconducting quantum wells have been shown to exhibit optical bistability when placed in a Fabry-Perot (Vivero, 2010), as does porous silicon (Pham, 2011).…”
Section: Nonlinear Resonators: Fabry-perots and Ringsmentioning
confidence: 99%
“…When the nonlinearity is saturating, it can be shown that if ∆n is the maximum refractive index change, then the condition for bistability is ∆nk o L > αL + (1-R eff ), where α is the (unsaturable) loss per unit length inside the cavity and R eff is the average mirror reflectivity (Garmire, 1989). Semiconducting quantum wells have been shown to exhibit optical bistability when placed in a Fabry-Perot (Vivero, 2010), as does porous silicon (Pham, 2011).…”
Section: Nonlinear Resonators: Fabry-perots and Ringsmentioning
confidence: 99%
“…[19][20][21] The use of applied currents with HF-bearing solutions makes integration with silicon-oninsulator platforms diffi cult. [21][22][23][24][25][26][27][28][29][30] To the best of our knowledge, the largest Q-factor is ∼3380 with a free-standing resonator [ 21 ] and ∼1530 for a multilayer resonator. [21][22][23][24][25][26][27][28][29][30] To the best of our knowledge, the largest Q-factor is ∼3380 with a free-standing resonator [ 21 ] and ∼1530 for a multilayer resonator.…”
mentioning
confidence: 99%